Short Review of Studies on Modeling of Technology and Technical Means Used for Production of Classical and Nanomodified Functional Polymer Composite Materials - E. Kolosov, A; P. Kolosova, E (International Journal of Engineering and Technology, 2018)
The paper briefly announces the results of many years of research in the field of modeling and design of parameters of technology and technical means for production of classical and nanomodified functional polymer composite materials for structural purposes. Models of oriented structurally inhomogeneous media are considered which form the basis for designing parameters for technological methods of impregnation and winding, as well as for predicting the stress-strain state of classical polymer composite materials. Ultrasonic treatment is being investigated as a basic method of intensifying technological processes as well as improving the physico-mechanical and operational properties of classical and nanomodified functional polymer composites. The main parameters and features of the ultrasonic treatment modes are described. The results of modeling and designing of manufacturing technology parameters for production thermoplastics are presented. The aspects of the production technology for nanomodified functional polymer composite materials for functional purposes are provided.Â Â